A class in sewing C.P.S. San Luis Obispo, Cal - Frank Aston::::::photographer::: (1909)
Women students in classroom, stitching by hand; instructor in background; sewing baskets on tables, table-top ironing board and electric iron; patterns drawn on blackboards (Published in 1908-09 Catalog (May 1909)